The system of procedural guarantees of the participants’ rights in criminal proceedings during pre-trial investigation - A. V. Piddubna (Bulletin of Kharkiv National University of Internal Affairs)
The current criminal procedural legislation of Ukraine contains legal guarantees designed to ensure proper protection, safeguarding and realisation of the rights, freedoms and legitimate interests of participants in criminal proceedings. However, in the legal literature, there is no unified approach to defining the essence and content of the system of procedural guarantees of the rights of participants to criminal proceedings, which negatively affects the functioning of the entire system of criminal procedural guarantees, its efficiency and effectiveness. The stability and effectiveness of the studied system of guarantees is an indicator of the level of development of many areas of public life and the legal status of an individual in the State. In this context, the issue of guaranteeing the rights, freedoms and legitimate interests of participants to criminal proceedings during the pre-trial investigation is controversial for both legislators and scholars, and is important for every citizen of Ukraine, since pre-trial investigation and criminal procedural activities in general are associated with interference with a person's private life and restriction of his or her rights, freedoms and legitimate interests in cases provided for by law.